PREDICTORS OF THE RISK OF HEMORRHAGIC EVENTS IN PATIENTS WITH ATRIAL FIBRILLATION RECEIVING LONGTERM THERAPY WITH DIRECT ORAL ANTICOAGULANTS - A. А. Sokolova; A. V. Zhilenko; I. L. Tsarev,; D. A. Napalkov; V. V. Fomin (Рациональная фармакотерапия в кардиологии)
Aim. To study the initial disorders in the coagulation system, as factors influencing the development of bleeding during anticoagulant therapy with direct oral anticoagulants (DOAC).Material and methods. 117 patients receiving DOAC (direct thrombin inhibitors – dabigatran, and Xa factor inhibitors – rivaroxaban and apixaban) were included into the cohort study in parallel groups. In addition to evaluate the efficacy and safety of therapy, an extensive analysis of the blood hemostasis system was performed in patients before the start of anticoagulant therapy.Results. No thromboembolic events and major bleedings were registered in patients receiving DOAC during 24 month observation. No significant correlations were observed between minor bleeding frequency in both groups (16.33% in dabigatran group and 22.39% in Xa factor inhibitors group) and troponin I and hemoglobin levels, as well as HAS-BLED and ATRIA risk scores. Among patients receiving dabigatran initial decrease in von Willebrand factor plasma level (p=0.02) and increase in fibrinogen blood concentration (p=0.02) were predictors of minor bleedings. These predictors of bleeding events were not found in Xa inhibitor groups.Conclusions. DOAC in patients with atrial fibrillation showed their efficacy and safety without any differences between classes of direct thrombin inhibitors and Xa factor inhibitors. Among the possible predictors of spontaneous minor hemorrhagic events on the dabigatran therapy, a reduced level of von Willebrand factor and elevated fibrinogen level may be considered when choosing a dose of the drug. Markers of hemorrhagic complications development were not determined for the Xa factor inhibitors. Limitation of this study was the absence of randomization, that is why the results should be interpreted with caution.